2022
DOI: 10.1007/s10067-022-06234-8
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 quarantine in adolescents with autoimmune rheumatic diseases: mental health issues and life conditions

Abstract: Objectives To assess mental health and life conditions in adolescents with autoimmune rheumatic diseases (ARDs) and healthy controls quarantined during COVID-19 pandemic. Method A cross-sectional study included 155 ARD adolescents and 105 healthy controls. Online survey included selfreported strengths and difficulties questionnaire (SDQ), and a semi-structured questionnaire with demographic data, daily home and school routine, physical activities, and COVID-19 information during the pandemic. Results Among pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Similar mental health behaviours were found to be worse in those with cSLE and other childhood rheumatic diseases during the pandemic. 36 We did find that socio-demographic factors such as having a first-degree relative with a psychiatric condition and experiencing neighborhood-level material deprivation increased the risk for depressive symptoms in cSLE patients. However, this association was not observed for anxiety symptoms.…”
Section: Discussionmentioning
confidence: 55%
“…Similar mental health behaviours were found to be worse in those with cSLE and other childhood rheumatic diseases during the pandemic. 36 We did find that socio-demographic factors such as having a first-degree relative with a psychiatric condition and experiencing neighborhood-level material deprivation increased the risk for depressive symptoms in cSLE patients. However, this association was not observed for anxiety symptoms.…”
Section: Discussionmentioning
confidence: 55%
“…Accumulating evidence suggests an increased emotional burden experienced by patients with chronic disease throughout the pandemic [ 7 , 17 , 18 ]. This burden has been compounded by limited access to medical care, fears related to underlying illness and risks related to COVID-19, as well as stressors related to quarantine and social distancing.…”
Section: Discussionmentioning
confidence: 99%
“…Other sources report a higher susceptibility to infection in patients with autoimmune diseases, either because of active autoimmune disease or because of the drugs used to treat them [7]. On the other hand, the results of other studies do not show an association between more severe COVID-19 trajectories in people with autoimmune diseases [6,7,87,88,90,92]. However, the results of some studies have suggested that people with autoimmune diseases may have a protective factor that would protect them from the most severe complications of COVID-19 as a result of taking medication [2,7,90].…”
Section: Covid-19 In Patients With Autoimmune Diseasesmentioning
confidence: 92%
“…Since the outbreak of the COVID-19 pandemic, many questions have been raised about the risk of SARS-CoV-2 infection and associated complications in people with autoimmune diseases [14,87]. It is still unclear whether or not autoimmune diseases pose a high risk of severe complications [2,6,7,14,15].…”
Section: Covid-19 In Patients With Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation